Legislative language and judicial politics: The effects of changing parliamentary language on UK immigration disputes. (August 2017) - Williams, Matthew
Why does the British government increasingly lose immigration cases in court? More broadly, what can explain the changing behaviour of appeal court judges? It is because government powers to manage immigration, delegated by Parliament, are increasingly couched in indeterminate language. Indeterminacy in legislation not only allows for executive discretion but also encourages litigation. Parliament has therefore provided the cause of action, and judges are not being 'activist'. This argument revitalises, with nuance, the legal model of judicial behaviour. New evidence supports the claim, with discourse analysis of all 1233 sections of immigration legislation enacted from 1905 to 2016 showing an increase in indeterminacy. Logit regression modelling of 252 immigration appeal cases between 1970 and 2012 shows that changes to language and the administration of the law can explain the outcome in 73% of cases.